Comparative study on the long jump's biomechanics in the case of athletes in major competitions - Costache, R. M.; Tifrea, C. (Logos, 2015)
Internationally, the research on motor skill biomechanics specific to various athletic events, in general, but in particular in technical events, including the long jump, has gained momentum. In recent decades, the evolution of athletic performances is a natural phenomenon of scientific researches which are carried out, generally, in sports and, in particular, in athletics. Despite all progress made so far, there are still inssufficiently cleared up issues on the role of dynamic and kinematic elements in terms of capitalizing upon the performance capacity in this event, especially in Romania. An important source for understanding and improving the technique of athletic events is the knowledge and application of biomechanics laws to the study and analysis of driving actions specific to athletic events. Athletic jumps can be defined as stylized driving actions used to pass over an obstacle, as tall as possible, or to cover horizontal distances during the leap, as long as possible. Getting some valuable performance in jumping events is conditioned by the following factors: - acquiring a high-efficiency technique; - reaching high speed during the run-up; - acquiring special expansion skills. In terms of the effort required, jumps are included in the group of events which need speed and explosive strength. The latter is closely related to the reactive force of the neuromuscular apparatus, able to pass quickly from a movement of active yield to a movement of active extension (stride).